Cardiopulmonary exercise testing before liver surgery. Issue 4 (4th June 2014) - Dunne, Declan F.J.; Jones, Robert P.; Lythgoe, Daniel T.; Pilkington, Francis J.; Palmer, Daniel H.; Malik, Hassan Z.; Poston, Graeme J.; Lacasia, Carmen; Jack, Sandy; Fenwick, Stephen W.
<x xml:space="preserve">Abstract</x> Background Cardiopulmonary exercise testing (CPET) assessed "poorer" fitness correlates with poorer outcomes in blinded studies. Whether this correlation will persist when CPET is utilized to stratify care as part of a multi‐modal enhanced recovery after surgery (ERAS) program is unclear. This study examined whether CPET variables were associated with postoperative morbidity in patients undergoing hepatectomy within an ERAS program. Objectives and Methods Data were prospectively collected on patients undergoing elective hepatectomy between October 2009 and April 2011. The relationships between CPET derived variables; postoperative complications and length of stay were investigated. Results Of 267 patients undergoing surgery, 197 had undergone standard cycle ergometer CPET. The relative oxygen uptake [<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghzffnzx8" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />VO2</alternatives> (ml kg−1 min−1)] and ventilatory equivalent of CO2<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghzffnzs6" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />(VE/VCO2)</alternatives> at the anaerobic threshold (AT) were not associated with complications or length of stay. Greater absolute oxygen uptake at AT [<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghzffnzrp" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />VO2</alternatives> at AT (L min−1)] was associated with early hospital discharge [OR 2.16 (95% CI 1.18–3.96), P = 0.013] on multivariable analysis. Conclusions When CPET is used to delineate perioperative management a low relative oxygen uptake [<alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pghzffnzv7" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />VO2</alternatives> (ml kg−1 min−1)] at the AT does not place patients at significantly higher risk of postoperative complications. This suggests CPET assessed "poor" fitness should not be used as a barrier to surgical intervention. J. Surg. Oncol. 2014; 110:439–444. © 2014 Wiley Periodicals, Inc.